THE USE OF LANGUAGE STYLE IN TELEVISION ADVERTISEMENT - Gusti Triawan; Tegar Prahara Putra (International Journal Labs, 2022)
The form of persuasion can be in the form of using language styles that can influence the audience's mindset so that they are interested in trying and buying the products offered. The problem that will be discussed in this research is what style of language appears and the meaning of language style in advertisements for facial cleansers, skin softeners, toothpaste, instant noodles, tea, butter, detergents, wafers, instant drinks, paints, and dairy products. This study aims to describe language styles that appear and the meaning of language styles in advertisements for various products on television. The method used is the analytical narrative method. The technique used is the recording and note-taking technique. The origin of the data is obtained from television advertisements downloaded from YouTube. The advertisements were chosen at random from a total of 20 that were broadcast on private television for the previous four years, from 2018 to 2021. The results of the study showed that the language styles that appeared in the advertisements were in the form of repetition, rhetoric, hyperbole, personification, metaphor, simile, synecdoche, metonymy, repetition, paradox, climax, alliteration, and parallelism.